Facebook news and (de)polarization: reinforcing spirals in the 2016 US election. Issue 7 (3rd July 2018) - Beam, Michael A.; Hutchens, Myiah J.; Hmielowski, Jay D.
ABSTRACT: The rise of social media, and specifically Facebook, as a dominant force in the flow of news in the United States has led to concern that people incur greater isolation from diverse perspectives through filter bubbles (from algorithmic filtering) and echo chambers (from an information environment populated by social recommendations coming from overwhelmingly like-minded others). This evolution in news diffusion comes at a time when Americans report increased affective partisan polarization. In particular, evidence shows increasingly negative attitudes about out-party members. Based on selective exposure and reinforcing spirals model perspectives, we examined the reciprocal relationship between Facebook news use and polarization using national 3-wave panel data collected during the 2016 US Presidential Election. Over the course of the campaign, we found media use and attitudes remained relatively stable. Our results also showed that Facebook news use was related to a modest over-time spiral of depolarization. Furthermore, we found that people who use Facebook for news were more likely to view both pro- and counter-attitudinal news in each wave. Our results indicated that counter-attitudinal news exposure increased over time, which resulted in depolarization. We found no evidence of a parallel model, where pro-attitudinal exposure stemming from Facebook news use resulted in greater affective polarization.